The influence of good corporate governance, corporate social responsibility, and sales growth on tax avoidance - Desi Jelanti (Jurnal Scientia, 2024)
This research uses quantitative research methods with a descriptive approach to examine the influence of Good Corporate Governance (GCG), Corporate Social Responsibility (CSR), and Sales Growth on Tax Avoidance. Secondary data from Energy and Technology sector companies on the Indonesia Stock Exchange during the 2018-2022 period was used in this research. The sampling method used was purposive sampling, with specific criteria to select 17 companies from 110 companies in the population. Data analysis techniques use statistical calculations with Microsoft Excel and Eviews 10. The research results show that GCG proxied by independent commissioners has a positive effect on Tax Avoidance, while GCG proxied by the audit committee shows no effect. CSR and Sales Growth have also been proven to affect Tax Avoidance positively. This research implies that it is essential for companies to consider these factors in their strategies and policies, while regulators need to strengthen regulations and supervision to prevent unethical Tax Avoidance practices.